Gravity model analysis: Robust evidence from the Czech Republic and corruption matching - Michal Paulus; Eva Michalíková (Charles University in Prague, Institute of Economic Studies (IES), 2014)
The results generally confirm that Czech trade is oriented towards European countries and determined primarily by key economic factors of domestic and foreign GDP. The institutional variables remain largely insignificant, except corruption due tothe counterintuitive result that a higher corruption level in partner country should boost mutual trade. We interpret this finding as a result of "corruption matching". The exclusion of outliers (LTS) significantly increases R-square and extends the number of significant determining factors (e.g. population or other institutional variables). The outliers, according to the LTS, are composed mainly of African, Asia and South or Central America states.
Keywords: C13; C23; F10; F12; F14; 330; Czech Republic; export; gravity model; fixed effects; LSDV; least trimmed squares